Failure analysis of Erosion-Corrosion of the bend pipe at sewage stripping units. (November 2021) - Yan, Zhenxing; Wang, Lida; Zhang, Piji; Sun, Wen; Yang, Zhengqing; Liu, Bingyan; Tian, Jisheng; Shu, Xiangquan; He, Yongpeng; Liu, Guichang
Highlights: Erosion-corrosion failure of the bend pipe of sewage stripper is studied. H2 S, NH3 and HCl build corrosive environment in bend pipe of sewage stripper. Inserted thermocouple induced non-uniform properties of fluid flow in bend pipe. Electrochemical corrosion and mechanical erosion dominate erosion-corrosion cycle. Abstract: Stainless-steel bend pipe is used to transport the media that contains H2 S and NH3 in sewage stripping unit. An obvious leakage occurs at the lateral wall and inner ridge of the elbow during service. Failure analysis is carried out by using traditional characterization techniques and computational fluid dynamics (CFD) simulation. Meanwhile, the effects of thermocouple length and elbow curvature radius on the failure behavior are also studied using numerical simulation methods. Results demonstrate that the high risk area obtained from CFD simulation coincides with the practical breakage area. Not only the corrosive medium dissolving in sewage contributes to the failure of the elbow, but also the inserted thermocouple leads to the uneven distribution of flow velocity inside the pipe which aggravates the local erosion-corrosion of the elbow. On the basis, a series of protective recommendations are put forward.